Juvenile Idiopathic Arthritis and Oculopathy - А.К. Pavlyuchenko (Zaslavsky O.Yu., 2012)
Oculopathies at juvenile idiopathic arthritis are diagnosed on 39 % of examined patients in correlation of «uveitis - cataract - conjunctivitis - glaucoma - scleritis - keratitis» as 10 : 5 : 4 : 4 : 2 : 1. At the same time, eye pathology is closely related to the integral clinical signs of the course of disease, determining the degree of activity and seropositivity of pathological process, affection of supramaxillary, knee joints and sacroiliac joints, and also extraarticular signs (changes of skin, lymph nodes, serous membrane, spleen), development of osteocystosis, osteousura and arhtroankylosis.